Marianus Pale Hera, Christology and Discipleship in John 17 (WUNT II/342; Tübingen: Mohr Siebeck 2013) - Darowski, Łukasz (The Biblical Annals, 2015)
Book review: Marianus Pale Hera, Christology and Discipleship in John 17 (WUNT II/342; Tübingen: Mohr Siebeck 2013). Pp. 206 + XIV. €64. ISBN 978-3-16-152219-2.